Fractional Calculus involving (p, q)-Mathieu Type Series - Kaur, Daljeet; Agarwal, Praveen; Rakshit, Madhuchanda; Chand, Mehar (Applied mathematics and nonlinear sciences, 2020)
Aim of the present paper is to establish fractional integral formulas by using fractional calculus operators involving the generalized ( , )-Mathieu type series. Then, their composition formulas by using the integral transforms are introduced. Further, a new generalized form of the fractional kinetic equation involving the series is also developed. The solutions of fractional kinetic equations are presented in terms of the Mittag-Leffler function. The results established here are quite general in nature and capable of yielding both known and new results.